2020
DOI: 10.5468/ogs.2020.63.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymph node ratio in surgically treated cases of vulvar cancer: a tertiary care centre experience

Abstract: ObjectiveThis study aimed to study the patterns of recurrence in surgically treated cases of vulvar cancer (VC) and determine the factors associated with recurrence, with a special emphasis on lymph node ratio (LNR). MethodsThis retrospective study examined VC patients primarily treated with surgery at our institute from January 2005 to December 2015. Demographic data, clinical characteristics, surgicohistopathological data, adjuvant treatment, follow up, and recurrence site and treatment were studied. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… 10 The majority of the recurrences that occurred were locoregional. In a study by Poddar et al, 22 in 61.9% of cases, local recurrence was the most common type, and most of it occurred in patients with initial lymph node metastasis. 22 Furthermore, Singareddy et al 23 showed that the locoregional occurrence rate was 24.5% in the radical surgery group, 12% in the surgery plus radiotherapy group, and 47% in the radical radiotherapy group, whereas the distant metastasis rate was only 4%.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 10 The majority of the recurrences that occurred were locoregional. In a study by Poddar et al, 22 in 61.9% of cases, local recurrence was the most common type, and most of it occurred in patients with initial lymph node metastasis. 22 Furthermore, Singareddy et al 23 showed that the locoregional occurrence rate was 24.5% in the radical surgery group, 12% in the surgery plus radiotherapy group, and 47% in the radical radiotherapy group, whereas the distant metastasis rate was only 4%.…”
Section: Discussionmentioning
confidence: 92%
“…In a study by Poddar et al, 22 in 61.9% of cases, local recurrence was the most common type, and most of it occurred in patients with initial lymph node metastasis. 22 Furthermore, Singareddy et al 23 showed that the locoregional occurrence rate was 24.5% in the radical surgery group, 12% in the surgery plus radiotherapy group, and 47% in the radical radiotherapy group, whereas the distant metastasis rate was only 4%. 21 In our study too, lymph node positivity was found to be an independent risk factor ( P < .05), but the common site of recurrences was distant.…”
Section: Discussionmentioning
confidence: 92%